THE IMPORTANCE OF TEACHING VOCABULARY, ITS ROLE AND SYLLABUS REQUIREMENTS. - Islamova Oydin Kamilovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article is about the correct use of dictionaries in English. Vocabulary teaching is the basis of language learning. Knowing a language means mastering its structure and words. Thus, vocabulary is one aspect of language taught in schools. Vocabulary is a collection of words and phrases to be taught and learned.